2007
DOI: 10.1088/0953-2048/21/01/015020
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of AC loss characteristics on the space in stacked YBCO conductors

Abstract: Four 5 mm wide YBCO conductors were assembled face to face to obtain a stacked YBCO conductor (YBCO stack). The space between the conductors composing the YBCO stack was set at 1.0 mm to investigate the influence of the space on AC loss characteristics. The magnetization losses without transport current, the transport losses without external magnetic field, and total AC losses of the YBCO stack carrying various transport currents in transverse magnetic fields with various orientations were measured. The measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 16 publications
3
32
1
Order By: Relevance
“…The auxiliary function g(x) = (2/x) ln(cosh(x)) − tanh x behaves as x 3 /6 at x 1 and its asymptote is 1 for x 1. The prediction of this model is surprisingly good, and Jiang et al [10] demonstrated that it can also be extended to angles differing from α = 90 • . However, when approaching the parallel configuration of the applied field, this modified strip model starts to deviate from the prediction.…”
Section: Ac Loss Of CC Tape On Non-magnetic Substratementioning
confidence: 80%
“…The auxiliary function g(x) = (2/x) ln(cosh(x)) − tanh x behaves as x 3 /6 at x 1 and its asymptote is 1 for x 1. The prediction of this model is surprisingly good, and Jiang et al [10] demonstrated that it can also be extended to angles differing from α = 90 • . However, when approaching the parallel configuration of the applied field, this modified strip model starts to deviate from the prediction.…”
Section: Ac Loss Of CC Tape On Non-magnetic Substratementioning
confidence: 80%
“…Interestingly, we see that the measured Bth values for the stack are significantly larger than the single conductor. We attribute this to a shielding effect from circulating current present in each wire in the stack [12,13]. This effect is more significant when the dc current value is small, and becomes weaker with increasing dc current.…”
Section: Experimental Methodsmentioning
confidence: 93%
“…Dynamic resistance is a form of hysteretic ac loss, and results in a parasitic heat load on the cryogenic system. For some high current applications, it is essential to assemble multiple HTS wires into stacks [12,13]. Therefore, it is important to understand the dynamic loss characteristics of HTS stacks carrying dc current when exposed to an external ac magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…For double (or single) pancake coils (or stacks of tapes) the magnetisation AC loss of stacks of tapes was simulated only for perpendicular applied fields in [23,24,20,25,21,26].The only measurements on the angular dependence of the AC loss are in [27]. However, there exists extensive work on coated conductors [28,29] and stacks of them [30,31,32]. All these measurements for single tapes and stacks were for coated conductors at an early stage of development, with poor artificial pinning and anisotropies approximately elliptical.…”
mentioning
confidence: 99%